Rational Syntheses of CdII and PbII Metal‐Organic Frameworks for Luminescence Sensing of Nitroaromatics, Ferric and Chromate Ions. Issue 2 (5th December 2016) - Wu, Yu; Li, Yulong; Zou, Like; Feng, Jianshen; Liu, Jianqiang; Luo, Miaomiao; Xu, Jingwen; Yadav, Reena; Kumar, Abhinav
Abstract : The metal‐organic frameworks (MOFs), [Cd(L)(H2 O)]· CH3 OH· DMF (1 ) and [Pb(L)(DMF)] (2 ) (L = 2, 4‐dihydroxybenzaldehyde nicotinoylhydrazone), were synthesized and characterized using microanalyses, IR spectroscopy, and single‐crystal X‐ray diffraction. Single crystal X‐ray analyses revealed that both1 and2 exhibit 2D grid networks. The photoluminescence investigation indicates that1 and2 could be a prospective candidate for developing luminescencent sensors for the selective sensing of nitrobenzene, which is used as a precursor for explosives. The luminescent properties of1 and2 in different solvents were investigated and corroborated by theoretical calculations. Additionally compounds1 and2 also show selective sensing ability for Fe 3+ as well as for CrO4 2– ions. Abstract :